Comparative analysis and meta-analysis of major clinical trials with oral factor Xa inhibitors versus warfarin in atrial fibrillation. Issue 1 (5th August 2014) - Nunes, José Pedro L; Rodrigues, Rui Paulo; Gonçalves, Francisco Rocha
Abstract : Objectives: A comparative analysis of three major clinical trials with factor Xa inhibitor oral anticoagulant (XOAC) drugs versus warfarin in atrial fibrillation—Rocket-AF (rivaroxaban), Aristotle (apixaban) and Engage AF Timi 48 (edoxaban; two different doses and sets of data)—was carried out. Methods: Data were extracted from the original reports (study level) and a meta-analysis was carried out. Results: When compared with warfarin, XOAC therapy was associated with a decrease in haemorrhagic stroke, with a similar pattern for all regimens and meta-analysis showing a risk ratio of 0.488 (95% CI 0.396 to 0.601). Regarding total mortality, a favourable pattern was seen for all four regimens and meta-analysis showed a risk ratio of 0.892 (95% CI 0.840 to 0.947). Major bleeding and gastrointestinal bleeding provided two examples regarding which heterogeneity would seem to exist, when XOAC drugs are compared with warfarin. In what concerns the incidence of myocardial infarction, the primary end point (stroke plus systemic embolism) and ischaemic stroke, the situation is less clear. These results are inconsistent with a putative 'group effect' for all the seven parameters under study, and for some of them it would probably be best to look at each of the individual trial data rather than at the meta-analysis data (which seem to lack a clear biological meaning). Conclusions: Apixaban, rivaroxaban and edoxaban have shown interesting effects, when compared with warfarin in clinical trials, in patients with atrial fibrillation, particularly with regard to haemorrhagic stroke and to the mortality rate. No other consistent conclusions concerning a putative 'group effect' can be reached at the present stage. Concerns regarding adherence to therapy, possible drug interactions, cost and current absence of antidotes may be taken into consideration when choosing an anticoagulant drug.